Ratting on wildlife crime: training African giant pouched rats to detect illegally trafficked wildlife - Szott, Isabelle D.; Webb, E. Kate; Mshana, Said; Mshigeni, Anthony; Magesa, Walter S.; Iyungu, Alexander; Saidi, Miraji; Van de Laak, Dian; Schneider, Miriam; Dore, Ashleigh; Brebner, Kirsty; Davies-Mostert, Harriet; et al. (Frontiers in Conservation Science, 2024)
The illegal wildlife trade (IWT) is one of the largest global crime economies, directly threatening species and their habitats, and biodiversity, and indirectly the global climate, and countries' economies. Syndicates operating within the IWT are often involved in trafficking of humans, weapons, and drugs. IWT takes place in large scale through international ports, with wildlife being smuggled inside shipping containers. Current methods to combat IWT and screen these shipping containers, such as X-ray scans, are expensive and time-consuming. Scent-detection animals present an innovative approach to combatting IWT, as animals may be better suited to distinguish between organic materials and less susceptible to visual concealment methods. Previous scent-detection work has largely focused on conservation dogs (Canis lupus familiaris). Here, we present a series of proofof-principle studies training African giant pouched rats (Cricetomys ansorgei) to detect illegally trafficked wildlife. Rats have low training and maintenance costs, flexibly work with multiple handlers, have a long lifespan, and a sophisticated sense of smell. Their small size also offers unique capabilities for the screening of shipping containers, such as being able to navigate densely packed areas or be lifted to assess contents of sealed containers by screening ventilation systems. As initial proof-of-principle within a controlled laboratory environment, we trained rats (n=11) to detect the scent of pangolin scales (Manis spp.) and a threatened African hardwood (Dalbergia melanoxylon).In subsequent experiments, we trained these rats (n=10) to detect rhinoceros horn (family Rhinocerotidae), and elephant tusks (Loxodonta spp.). At the conclusion of these studies, rats (n=7) accurately identified all four target species (although ivory samples may have been crosscontaminated, and results should be interpreted with caution) while correctly rejecting non-target items commonly used by traffickers to conceal the presence of illicit material. Rats detected the presence of wildlife targets even when these were concealed in mixtures among non-target items. These results provide the foundation to train rats for scent-detection of illegally trafficked wildlife to combat IWT. The unique attributes of rats could allow them to complement existing screening technologies in the fight against IWT. Future directions include assessing operational feasibility of deploying rats at ports.